Optimizing Workplace Performance: Unraveling the Impact of Salary, Incentives, and Job Satisfaction at PT. Printec Perkasa I, Tangerang City - Firmansyah, Ade; Rosyid, Rosyid (PT. Batari Edu Calya, 2023)
This study investigates the impact of salary, incentives, and job satisfaction on the work productivity of employees at PT. Perkasa Printec I Tangerang City. A total of 65 employees were surveyed using probability and nonprobability sampling techniques. The results showed a positive and significant relationship between salary and employee productivity, with a unidirectional relationship. Incentives also had a positive and significant effect on productivity, with a direct relationship between the variables. Job satisfaction had no negative and insignificant effect on productivity. The partial test (T test) showed that salary had a positive and significant effect on productivity, while incentives had a positive and significant effect. Job satisfaction had a negative and partially insignificant effect on productivity, with a significant value of 0.127. The study concludes that salary, incentives, and job satisfaction play crucial roles in determining employee productivity.